Copper removal from acid mine drainage-polluted water using glutaraldehyde-polyethyleneimine modified diatomaceous earth particles. Issue 2 (February 2018) - Larsson, Mikael; Nosrati, Ataollah; Kaur, Simarpreet; Wagner, Jochen; Baus, Ulf; Nydén, Magnus
Abstract: Mine waters and tailings generated from mining and mineral processing activities often have detrimental impact on the local environment. One example is acid mine drainage, in which sulphides in the mining waste react with water and oxygen to produce an acidic environment that subsequently dissolves host rock minerals from the waste containing toxic metals and trace elements. Copper is one such metal of significance, as it is mined at large volumes in sulphide containing ores. It has strong biocidal activity that greatly affects ecosystems. We have previously reported that glutaraldehyde (GA)-crosslinked polyethyleneimine (PEI) has strong affinity and selectivity for copper and that diatomaceous earth (DE) particles can be modified with the material to form a copper-extraction resin. In this study, the copper uptake of GA-PEI-DE particles was investigated from synthetic and real acid mine drainage samples under different pHs and their copper removal performance was compared with that of selected commercial resins. The results revealed that copper could effectively and preferentially bind to the material at pH 4, and that the copper could be completely eluted by lowering of the pH. In addition, effective copper uptake and elution was demonstrated using real legacy acid mine drainage water from Mount Lyell in Tasmania.